2019
DOI: 10.1111/geb.13000
|View full text |Cite
|
Sign up to set email alerts
|

On the mismatch in the strength of competition among fossil and modern species of planktonic Foraminifera

Abstract: Aim Many clades display the macroevolutionary pattern of a negative relationship between standing diversity and diversification rates. Competition among species has been proposed as the main mechanism that explains this pattern. However, we currently lack empirical insight into how the effects of individual‐level ecological interactions scale up to affect species diversification. Here, we investigate a clade that shows evidence for negative diversity‐dependent diversification in the fossil record and test whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 88 publications
(185 reference statements)
1
8
1
Order By: Relevance
“…The importance of diversity-dependence over most of the time and for both speciation and extinction rates is congruent with previous studies dealing with different animal and plant clades, time intervals and geographical regions [1,2,4,22,26,5759]. These studies involve a number of invertebrate taxa, including marine gastropods [60].…”
Section: Discussionsupporting
confidence: 87%
“…The importance of diversity-dependence over most of the time and for both speciation and extinction rates is congruent with previous studies dealing with different animal and plant clades, time intervals and geographical regions [1,2,4,22,26,5759]. These studies involve a number of invertebrate taxa, including marine gastropods [60].…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the complete species diversity of planktonic foraminifera has been described for the Plio-Pleistocene, with good agreement between morphological and molecular phylogenies (22,(25)(26)(27). Although some have speculated that foraminifera competitively exclude each other (24), recent work found that planktonic foraminifera species seldom restrict each other's distributions (28). Presumably, therefore, species occupy the full envelope of existing environmental conditions within their tolerance limits, and geographic distributions are determined almost entirely by physical ocean conditions.…”
mentioning
confidence: 94%
“…However, few of these studies were conducted in marine environments, and almost no work extended beyond 10 years and 1,000 km 2 [4,5]. In limited investigation of marine taxa at larger spatiotemporal scales, macroecologists and paleobiologists have observed little evidence of competitive exclusion [6][7][8][9]. Here, we quantified spatial trends in the rich and densely sampled fossil history of brachiopods and bivalves, while accounting for inconsistent sampling coverage through time using a new method of spatial standardization.…”
mentioning
confidence: 99%